ILCOR World Restart a Heart – Spreading global CPR awareness and empowering communities to save lives since 2018 - N. Rott; L. Reinsch; B.W. Böttiger; A. Lockey (Resuscitation Plus)
The International Liaison Committee on Resuscitation (ILCOR) World Restart a Heart (WRAH) Initiative is helping to save countless lives by promoting a culture of preparedness and encouraging widespread lay cardiopulmonary resuscitation (CPR) training. In total from 2018 to 2023 at least 12.6 million people were trained, and 570.7 million people were reached, showing a variety of campaigns adapted to countries current situation and their culture. World Restart a Heart success is based on an annual collaboration between nations, organisations and communities, demonstrating its universal relevance and impact. Because of this it is able to adapt to varies different circumstances and presents an accessible and effective solution to a significant global health problem, saving many lives over the years by promoting bystander CPR.